2014
DOI: 10.1002/jmri.24592
|View full text |Cite
|
Sign up to set email alerts
|

MR pulse wave velocity increases with age faster in the thoracic aorta than in the abdominal aorta

Abstract: The thoracic aorta is less stiff than the abdominal aorta in young and middle-aged subjects, and stiffens more rapidly with age than the abdominal aorta, resulting in a stiffer thoracic than abdominal aorta at older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…The similar growth of proximal and distal sections entails a reduction of pulse pressure amplification with age, as found in several clinical studies [22,24,31,[45][46][47]. Moreover, the increase of characteristic impedance along the aorta is dampened with age [48]: from 20 to 80 years of age, abdominal values of Z C change from being 8 to 5 times the characteristic impedance at the aortic root and, in particular, in the thoracic aorta the increase reduces from +150% to +80% in the same age range (see panel 3d). It follows that the spatial gradient of systolic pressure upstream the thoracic aorta is reduced, contributing (from upstream) to smooth away the peak.…”
Section: Resultssupporting
confidence: 62%
“…The similar growth of proximal and distal sections entails a reduction of pulse pressure amplification with age, as found in several clinical studies [22,24,31,[45][46][47]. Moreover, the increase of characteristic impedance along the aorta is dampened with age [48]: from 20 to 80 years of age, abdominal values of Z C change from being 8 to 5 times the characteristic impedance at the aortic root and, in particular, in the thoracic aorta the increase reduces from +150% to +80% in the same age range (see panel 3d). It follows that the spatial gradient of systolic pressure upstream the thoracic aorta is reduced, contributing (from upstream) to smooth away the peak.…”
Section: Resultssupporting
confidence: 62%
“…The similar growth of proximal and distal sections entails a reduction of pulse pressure amplification with age, as found in several clinical studies [ 22 , 24 , 31 , 45 47 ]. Moreover, the increase of characteristic impedance along the aorta is dampened with age [ 48 ]: from 20 to 80 years of age, abdominal values of Z C change from being 8 to 5 times the characteristic impedance at the aortic root and, in particular, in the thoracic aorta the increase reduces from +150% to +80% in the same age range (see panel 3 d ). It follows that the spatial gradient of systolic pressure upstream the thoracic aorta is reduced, contributing (from upstream) to smooth away the peak.…”
Section: Resultsmentioning
confidence: 99%
“…abdominal aortic stiffness with aging and the mechanisms involved 68, 1720 , despite the clinical importance of this topic for renal perfusion or for abdominal aortic aneurysm, which exceeds thoracic in frequency 21 . There is even relatively little known about regional aortic stiffness and its mechanisms in the absence of aging 1719 . The present investigation addressed these topics and the results were significant in two major areas; 1) the mechanisms of aortic stiffness that differ with aging, and 2) the differences in aortic stiffness and its mechanisms in the thoracic vs. abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly some studies even showed an increase in elastin 27, 31 , which should act to decrease aortic stiffness. As noted above, fewer studies have examined both thoracic and abdominal aortic stiffness with aging, in vivo 68, 1720 . Although isolated in vitro studies have found that abdominal stiffness is increased more with aging 32 , most prior studies, in vivo, found that increases in thoracic aortic stiffness with aging were greater than, or similar to that of abdominal aortic stiffness 68, 1720 which is the reverse of our data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation